Comparison of cord blood CD34 + stem cell expansion in coculture with mesenchymal stem cells overexpressing SDF‐1 and soluble /membrane isoforms of SCF. Issue 9 (17th May 2019) - Ajami, Mansoureh; Soleimani, Masoud; Abroun, Saeid; Atashi, Amir
Abstract: Aim: Umbilical cord blood hematopoietic stem cells (UCB HSCs) have been considered for the treatment of hematological malignancies due to their noninvasive collection, greater capacity of expansion, and remarkable tolerance for HLA mismatch in transplantation. On the other hand, the most considerable limitation of these cells is their inadequate amount of CD34 + HSCs which leads to delayed engraftment. The aim of this study was the expansion of CD34 + HSCs by coculturing with mesenchymal stem cells (MSCs) overexpressing stromal cell‐derived factor‐1, soluble and membrane isoforms of stem cell factor (sSCF/mSCF). Keeping structure and function of overexpressed cytokines by MSCs was expected which could beneficially affect the CD34 + HSC expansion. Methods: MSCs and CD34 + HSCs were isolated from UCB mononuclear cells. UCB MSCs were nucleofected with one or more of sSCF, mSCF, and SDF‐1 expression vectors. Isolated CD34 + HSCs were then cocultured with nucleofected MSCs in 10 groups in culture medium containing TPO and Flt3L with or without SCF (3F or 2F groups). Then the CD34 + HSCs numeration, clonogenic capacity, and transcriptional levels of well‐known HSCs regulatory and stemness genes (CXCR4, HOXB4, BMI1, and SALL4) were assessed following coculture with modified MSCs. Results: CD34 + HSCs which expanded on MSCs overexpressing mSCF/sSCF/SDF‐1 in the 3F group showed the most significant increase in the expansion (4.73 ± 0.26 fold), clonogenic capacity (5.3 ± 0.25 fold) and also transcriptional levels of CXCR4, HOXB4, and BMI1 (3.49 ± 0.13, 9.49 ± 0.78, and 11.6 ± 0.9 fold), respectively ( P < 0.05). Conclusion: Overexpression of SCF and SDF‐1 by UCB MSCs in coculture system has efficient effect on UCB HSCs expansion. Furthermore nucleofected MSC overexpressing either sSCF/mSCF or mSCF/ sSCF /SDF‐1 could substitute the rhu SCF in HSC expansion culture medium. Abstract : 1.Previous studies have reported the striking role of stromal cell‐derived factor 1 (SDF‐1) and stem cell factor (SCF) as prominent mesenchymal stem cell (MSC)‐produced growth factors on ex vivo expansion of hematopoietic stem cells especially in direct interactions. 2. Expanded CD34 + HSCs in coculture with MSCs overexpressing mSCF/sSCF /SDF‐1 were indicated the most significant increase in expansion, clonogenic capacity and transcript levels of CXCR4, HOXB4, and BMI1 genes.